2020
DOI: 10.1002/ppul.25046
|View full text |Cite
|
Sign up to set email alerts
|

Digital auscultation in PERCH: Associations with chest radiography and pneumonia mortality in children

Abstract: Background: Whether digitally recorded lung sounds are associated with radiographic pneumonia or clinical outcomes among children in low-income and middleincome countries is unknown. We sought to address these knowledge gaps. Methods: We enrolled 1 to 59 month old children hospitalized with pneumonia at eight African and Asian Pneumonia Etiology Research for Child Health sites in six countries, recorded digital stethoscope lung sounds, obtained chest radiographs, and collected clinical outcomes. Recordings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…We have shown that lung sound classifications of digital auscultation recordings generated using a listening panel approach has strong associations with radiographic findings and also mortality outcomes 48 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have shown that lung sound classifications of digital auscultation recordings generated using a listening panel approach has strong associations with radiographic findings and also mortality outcomes 48 .…”
Section: Discussionmentioning
confidence: 94%
“…In this study we will utilize the paediatrician listening panel as our gold standard reference as previously described 40 . We have shown that lung sound classifications of digital auscultation recordings generated using a listening panel approach has strong associations with radiographic findings and also mortality outcomes 48 .…”
Section: Discussionmentioning
confidence: 94%
“…40 We have shown that lung sound classifications of digital auscultation recordings generated using a listening panel approach have strong associations with radiographic findings and also mortality outcomes. 48 Open access work ranges from additionally refining this device, based on lessons learnt from the use of the device at the first-level facility during this study as well as phases 1 and 2 clinical trials that prospectively integrate the digital auscultation into the WHO pneumonia management pathway to evaluate patient outcomes after digital auscultation-based decision-making. Eventually, if these preliminary studies are successful, a large multicountry clinical trial could be designed to evaluate the safety and efficacy of digital auscultation to improve pneumonia management.…”
Section: Discussionmentioning
confidence: 99%
“…Ajay C. Kevat MBBS, MMed, MPH, FRACP 1,2 Fazeah Marzbanrad BSc, MSc, PhD 3 Robert Roseby MBBS, FRACP 4,5…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…The authors of the recently published article “Digital auscultation in PERCH: Associations with chest radiography and pneumonia mortality in children” 1 deserve to be congratulated on their exploration of an innovative approach to the longstanding clinical conundrum of how best to differentiate potentially life‐threatening pneumonia from less severe childhood respiratory illnesses. Utilizing digital stethoscope (DS) technology, they collected breath sound samples from several hundred unwell young children across six different developing nations.…”
mentioning
confidence: 99%